Variation in Medicaid and commercial coverage of cell and gene therapies - Molly T. Beinfeld; Julia A. Rucker; Nola B. Jenkins; Lucas A. de Breed; James D. Chambers (Elsevier, 2023)
Growth in the availability of cell and gene therapies (CGTs) promises significant innovation in the treatment of serious diseases, but the high cost and one-time administration of CGTs has also raised concern about strain on health plan budgets and inequity in access. We used coverage information from the Tufts Medical Center Specialty Drug Evidence and Coverage (SPEC) database for 18 large commercial health plans in the US and information from state Medicaid websites to examine variation in coverage of 11 CGTs in August 2021. We found that US commercial and Medicaid health plans imposed restrictions in 53.5 % and 68.3 % of their coverage policies for the 11 included CGTs, respectively. In addition, we identified significant variation in access to CGTs across commercial plans and across Medicaid plans. Coverage restrictions for certain CGTs were more common than others; clinical requirements were often (but not always) consistent with the inclusion criteria for the clinical trial central to the drug's approval. We conclude that there is variation in access to CGTs, creating differential patient access.